2022
DOI: 10.1002/jev2.12281
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and efficient isolation platform for plasma extracellular vesicles: EV‐FISHER

Abstract: Extracellular vesicles (EVs) have found diverse applications in clinical theranostics. However, the current techniques to isolate plasma EVs suffer from burdensome procedures and limited yield. Herein, we report a rapid and efficient EV isolation platform, namely, EV-FISHER, constructed from the metal-organic framework featuring cleavable lipid probes (PO 4 3− -spacer-DNA-cholesterol, PSDC). The EV-FISHER baits EVs from plasma by cholesterol and separates them with an ordinary centrifuge. The captured EVs coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This new diagnostic approach offers insights into the diagnosis of BEVs 64 . In recent years, new technologies, such as EV‐FISHER, 65 aptamer‐based methods, 66 and droplet‐based single‐exosome‐counting, 67 have enabled the development of diagnostic BEVs. Previous study on diagnostic BEVs …”
Section: The Potential Of Bevs In Clinical Applicationmentioning
confidence: 99%
“…This new diagnostic approach offers insights into the diagnosis of BEVs 64 . In recent years, new technologies, such as EV‐FISHER, 65 aptamer‐based methods, 66 and droplet‐based single‐exosome‐counting, 67 have enabled the development of diagnostic BEVs. Previous study on diagnostic BEVs …”
Section: The Potential Of Bevs In Clinical Applicationmentioning
confidence: 99%
“…EVs carry a variety of biomolecules inherited from their parent cells (including nucleic acids, proteins, lipids and metabolites), and are involved in a wide range of physiological and pathological processes (Mathieu et al., 2019). Notably, many tumour‐derived EV proteins have been identified as important biomarkers for early cancer diagnosis (Pan et al., 2022; Qian et al., 2022; Xu et al., 2018), where the type and expression levels of EV proteins can indicate the cancer classification and progression status (van Niel et al., 2018). However, the small clinical sample volumes, confounded with interference by non‐EV components and the normally low expression levels of target proteins pose great challenges for specific EV isolation and protein analysis (Yu et al., 2022), both of which are necessary for an accurate clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…as important biomarkers for early cancer diagnosis (Pan et al, 2022;Qian et al, 2022;Xu et al, 2018), where the type and expression levels of EV proteins can indicate the cancer classification and progression status (van Niel et al, 2018). However, the small clinical sample volumes, confounded with interference by non-EV components and the normally low expression levels of target proteins pose great challenges for specific EV isolation and protein analysis (Yu et al, 2022), both of which are necessary for an accurate clinical diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, EVs have been found in a variety of physiological fluids including blood, urine, saliva, breast milk, amniotic fluid, ascites, cerebrospinal fluid, bile, and semen [ 8 , 9 , 10 , 11 , 12 ]. More importantly, EVs can be directly isolated from physiological fluid in solid organs including the liver, heart, brain, and others [ 13 , 14 , 15 , 16 , 17 ]. Originally, the majority of studies focused on clinical diagnosis; however, in recent years, EVs have shown a bright future as an excellent therapeutic vehicle for treating diseases, especially cancer.…”
Section: Introductionmentioning
confidence: 99%